Planetary bioengineering on Earth to return and maintain the atmospheric carbon dioxide to pre-industrial levels: Assessing potential mechanisms - Moore, David; Heilweck, Matthias; Petros, Peter (Frontiers in Astronomy and Space Sciences, 2022)
The living things that have arisen on this planet have been modifying their habitats on Earth since they first appeared. Modifications that include the greening of Earth by photosynthetic organisms, which turned a predominantly reducing atmosphere into an oxidising one, the consequent precipitation of iron oxides into iron ore strata, and the formation of huge deposits of limestone by calcifying organisms. The episodes on which we wish to concentrate are (a) the frequent involvement of marine calcifiers (coccolithophores, foraminifera, molluscs, crustacea, corals, echinoderms), that have been described as ecosystem engineers modifying habitats in a generally positive way for other organisms, and (b) the frequent involvement of humans in changing the Earth’s biosphere in a generally negative way for other organisms. Our core belief, that humankind must look to the oceans for a solution to climate change since periodically, over the past 500 million years, the fossil record shows that ancestral marine calcifiers had the physiology to cope with both acidified oceans and great excesses of atmospheric CO2, creating vast remains of shell as limestone strata. The marine calcifiers of this planet have a track record of decisively modifying both acidified atmospheres and atmospheres containing excess CO2 but take millions of years to do it. On the other hand, humanity works fast; in just a few thousand years we have driven scores of animals and plants to extinction, and in just a few hundred years we have so drastically modified our atmosphere that we stand on the verge of extinction ourselves. Of all Earth’s ecosystems, those built around biological calcifiers, which all convert organic carbon into inorganic limestone, are the only ones that offer the prospect of permanent net removal of CO2 from our atmosphere. These are the carbon-removal biotechnologies we should be seeking to exploit.